Ability of the Saccharomyces cerevisiae Y904 to tolerate and adapt to high concentrations of selenium - Amorim Mota, Layna; Maria da Silva, Ana Paula; Alberto da Silva, Eric; Maria Ferreira Lima Leite, Gabriela; Perez Calegari, Rubens; Sampaio Baptista, Antonio (Revista Brasileira de Engenharia de Biossistemas, 2022)
The alcoholic fermentation industry generates a large surplus of yeasts, which, in turn, have the ability to bioaccumulate minerals and enable their bioavailability after cell autolysis. Among these minerals, selenium (Se) stands out, which participates in the formation of antioxidant enzymes. The objectives of the work were to define the minimum and maximum concentration of Se that yeasts (Saccharomyces cerevisiae – Y904) support and the concentrations that they tolerate once adapted. To this end, a test of tolerance to Se was carried out, using treatments with different concentrations of Se. The adaptive process started at the maximum concentration obtained in the tolerance test of 60 mg mL-1, with increasing addition of 6 mg mL-1, reaching up to 246 mg mL-1 of Se. The macromorphological characteristics and number of colony forming units (CFU) were evaluated. It was identified that yeasts without adaptation grew on substrate containing up to 60 mg mL-1 of Se and those adapted, up to 246 mg mL-1 of Se. In addition to the reduction in yeast growth speed, from the concentration of 84 mg mL-1 of Se in the medium, morphological changes in colony color were observed. It is concluded that non-adapted yeasts support up to 60 mg mL-1 of Se and, after the adaptive process, they support 246 mg mL-1 of Se in the medium after the adaptive process, which adds value to the final product, and makes yeasts suitable for human nutrition as a supplement or even in the formulation of probiotics.